Decision Making System for Preparation of Village Annual Work Plans and Budgets Using the AHP Method - Jenerivani Katarina Br Ginting (Institute of Computer Science, 2019)
This research is a Decision Making System for the preparation of work plans and annual village budget with the AHP method. The AHP method is used for the preparation of the work plan and annual village budget which is determined based on the criteria of time, funds, jlh / vol in determining the best alternative. This Decision Making System was built with the Visual Studio 2010 application as a tool in the preparation of the annual village work plan and budget and using MYSQL as a database. The outcome of the Decision Making System is the Taking System. Decision on the preparation of the work plan and the annual village budget helps the village apparatus in submitting the work plan and annual village budget.